Effectiveness of an Avatar application for teaching heart attack recognition and response: A pragmatic randomized control trial. (17th November 2019) - Tongpeth, Jintana; Du, Huiyun; Barry, Tracey; Clark, Robyn A.
Abstract: Aims: To evaluate the effectiveness of an Avatar application for educating people with acute coronary syndrome (heart attack). Background: A lack of understanding of Acute Coronary Syndrome symptoms and appropriate responses often contribute to delay in seeking medical treatment. Design: A single‐centre, non‐blinded, pragmatic randomized controlled trial. Methods: Seventy Acute Coronary Syndrome patients were randomly assigned to the intervention (Avatar application) or usual care groups. Participants were followed up at 0, 1, and 6 months. Tobit Growth Curve Model was used to analyse the primary outcome—symptom knowledge; and the secondary outcomes—attitudes and beliefs. Heart attack action plan implementation and health care utilisation were analysed using Chi‐square and Mann–Whitney U test. Results: Of the 70 participants, 63% were male and the mean age of the participants was 64.7 ( SD 11.7) years. Sixty‐six (94.2%) participants completed follow‐up. Between group differences on acute coronary syndrome (ACS) Response Index scores were statistically significant at 1‐month and 6‐month follow‐ups ( p  < .01). The intervention group had a significant improvement in symptom knowledge, attitudes, and beliefs over the 6‐month period ( p  < .001, p  = .009, p  < .001 respectively); and no significant improvement in the usual care group participants ( p  = .152, p  = .068, p  = .228). For healthcare use, at follow‐up, there was a significant difference in ambulance use, between the intervention group and the usual care group (33.33% vs. 18.18%, p  = .008; cardiac: 88.89% vs. 42.86%; p  = .049); 85.14% of participants reported that the application helped them to feel more confident in recognizing and responding to symptoms in the future. Conclusion: The education app was effective in improving individuals' ACS knowledge, attitudes, and beliefs. A large multi‐centre trial with a longer follow‐up to evaluate the intervention's effectiveness on clinical outcomes will be our next step in evaluation. Impact: The content of AVATARS (Nurse Cora) app can be translated into different languages and evaluated for patients from different health settings and linguistic backgrounds. Trial Registration: This study has been registered with Australian New Zealand Clinical Trials Registry (ANZCTR). The trial registration number is ACTRN12616000803493. Abstract : 目的: 评估Avatar应用于急性冠状动脉综合征(心脏病)患者教育的有效性。: 背景: 缺乏对急性冠状动脉综合征症状和正确应对方法的了解, 往往导致延误就医。: 设计: 单中心、非盲、实用随机对照试验。: 方法: 将70位急性冠状动脉综合征患者随机分为干预组(Avatar应用组)或常规护理组。分别在0、1和6个月内随访试验参与者。采用Tobit生长曲线模型来对症状知识进行初级结果分析;其次是对态度和信念进行2次结果分析。使用China ‐ square和Mann‐Whitney U测试分析心脏病发作行动计划的实施和卫生保健的使用情况。 结果: 在70名参与者中, 63%为男性, 平均年龄为64.7岁(SD 11.7)。66名(94.2%)参与者完成了随访。根据1个月到6个月的跟踪访问, 因为不同组间的急性冠状动脉综合征(ACS)的不同, 反应指数评分统计数据也大有不同 (p < .01)。干预组在6个月内症状知识、态度和信念有显著提高(p < .001, p = .009, p < .001);常规护理组参与者无明显提高(p = .152, p = .068, p = .228)。在使用医疗服务方面, 干预组和常规护理组在使用救护车方面有显著差异(33.33% vs.18.18%, p = .008;心脏:88.89% vs. 42.86%;p = .049);85.14%的参与者表示, 该应用帮助他们在未来识别和应对症状时更有信心。 结论: 教育应用程序能帮助有效提高ACS患者的知识、态度和信念。我们下一步的评估工作将是一项大型多中心试验, 随访时间更长, 以评估干预措施对临床结果的有效性。 影响: AVATARS (Nurse Cora)应用程序的内容可以被翻译成不同的语言, 并为来自不同健康环境和语言背景的患者评估病情。 试验注册: 本研究已在澳大利亚‐新西兰临床试验注册中心(ANZCTR)注册。试验注册号为ACTRN12616000803493。